Reel help for real life: Film therapy and beyond - Strong, Philippa (HTS teologiese studies, 2015)
In this article the background, development, therapeutical value and praxis of film therapy in Christian counselling will be addressed. The second part of the article shows what the scenery beyond film therapy may look like and how this form of therapy may extend to other areas of digital and electronic media in the current counselling and pastoral care praxis. Postmodernity, as the context within which the society finds itself, is discussed, as well as the place of films in postmodernity. The important use and application of narratives in the postmodern era is discussed. Film therapy’s development as an outgrowth of bibliotherapy is explained. It is further shown how film therapy as a tool in the praxis of therapy may provide the ideal atmosphere for learning, enjoyment and edification. The scope of the article also reaches beyond the current use of film therapy by suggesting the use of other social and electronic media in a therapeutical way as an ever-increasing possibility. The article ends with some pointers in the use of film therapy.